Feel the heat - Gerard, Cindy (New York : Pocket Star Books, 2009)
Gorgeous Black Ops bad boy Raphael Mendoza always feared his family's dark history would haunt him. But he never expected it might hold the key to dismantling a rogue weapons system. Now with cool B. J. Chase posing as his hot babe fiancee, he returns to his uncle in Colombia to convince him he can be trusted with the family's dirtiest business secrets as the countdown to international catastrophe closes in.
Keywords: Man-woman relationships -- Fiction; Families -- Fiction; Romantic suspense fiction